Functionality of internal control in cities: a study in the municipality of a metropolitan area of brazil northeast - Vasconcelos, Marco Tullio de Castro; Sampaio, Francisco Jean Carlos de Souza; Silva Neto, Antonio Firmino da; Duque, Celma (Advances in Scientific and Applied Accounting, 2013)
This study examines how it has been developed the Internal Control in the prefectures of the metropolitan area of Natal in Rio Grande do Norte. The inductive method was used, considering that it aimed to analyze the Internal Control developed by municipalities in a particular way and has used the literature and through field interviews and the application of semi-structured questionnaire designed in the light of theory and relevant legislation for data collection. The composition of the sample is not probabilistic intentional, chosen by criterion of accessibility. There was an interview and questionnaire application with the sector responsible for controlling the local governments. The targets set by the municipalities, approximately 37% of the targets were fulfilled with the aid of internal control. The public administration does not demystify the concept that internal controls are in place just to meet legal requirements. The effectiveness of these controls in the metropolitan area of Natal was not evident in the work.